PERBANDINGAN JUMLAH PROPORSI CAMPURAN DAN KEKUATAN MEKANIK BETON BERDASARKAN SNI 03-2834-2000 DAN SNI 7656:2012 - Suku, Yohanes Laka; Dhema, Yovita Yoanata (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2024)
The current concrete mix design is still based on the guidelines in SNI 03-2834-2000 which refers to Departement of Environment (DoE), Building Research Establishment, Britain and SNI 7656: 2012 which refers toAmerican Concrete Institute (ACI) 211.1-91. This study analyzes the differences between the standards SNI 7656:2012 and SNI 03-2834-2000 in designing concrete mixtures with a target compressive strength of 20 MPa. The analysis results show that SNI 7656:2012 uses less coarse aggregate, cement, and water, specifically 4.39%, 23.07%, and 16.35% less, respectively, but uses 41.75% more fine aggregate compared to SNI 03-2834-2000. The concrete designed using SNI 03-2834-2000 resulted in higher average compressive strength by 25.82%, higher tensile splitting strength by 46.27%, and higher flexural strength by 18.93%. However, the rate of strength development at 14 days was faster for concrete designed with SNI 7656:2012, with increases of 14.37% in compressive strength, 13.53% in tensile splitting strength, and 9.69% in flexural strength. Additionally, the water-cement ratio (WCR) and the proportion of aggregate mixtures were found to have a significant impact on concrete strength; a lower WCR and a higher proportion of coarse aggregate tend to increase concrete strength.